EFEKTIVITAS METODE PEMBELAJARAN KNOW TO KNOW LEARNED (KWL) TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS KELAS IV SDN 03 TANJUNG BATU - Niswatun Adzka; Kiki Aryaningrum; Sunedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effectiveness of the Know Want To Know Learned (KWL) learning method on the Social Studies learning outcomes of fourth-grade students at SD Negeri 03 Tanjung Batu. The research employed a quantitative experimental method using a Pretest-Posttest Control Group Design. The sample consisted of 44 fourth-grade students, including 22 students from Class IV A as the control group and 22 students from Class IV B as the experimental group. Data were collected through tests, observations, and documentation. Data analysis was conducted using normality tests, homogeneity tests, and hypothesis testing through the independent sample t-test. The results showed that the average pretest score of the control class increased from 46 to 63 on the posttest, while the average pretest score of the experimental class increased from 68 to 82 on the posttest. The hypothesis test revealed that the t-value was 11.41 and the t-table value was 2.018 at a significance level of 5%, indicating that t-value > t-table (11.41 > 2.018). Therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. It can be concluded that the Know Want To Know Learned (KWL) learning method is effective and has a significant effect on the Social Studies learning outcomes of fourth-grade students at SD Negeri 03 Tanjung Batu.